2008
DOI: 10.4314/sajas.v38i1.4110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term pre-hatch heat shock of incubating eggs on subsequent

Abstract: ________________________________________________________________________________ AbstractThe aim of this study was to investigate the effect of thermal conditioning of broiler chickens during embryonic development on subsequent performance under standard rearing conditions. During incubation eggs from 32-, 45-and 56-week old Ross 308 broiler parent stock were subjected to a 2 h heat shock of 39 °C on days 14 and 15 of incubation. Eggs in the control were incubated throughout incubation at 37 °C. Chicks were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…In contrast, studies by 41 43 , demonstrated that a decrease in body weight from hatching until 6 weeks of age for chicks hatched from eggs exposed to different thermal conditioning regimes. Sengor et al 41 exposed eggs to TC at 39 °C for 2 h per day at E14 and E15, while 42 subjected eggs to 39.6 °C or 40.6 °C.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, studies by 41 43 , demonstrated that a decrease in body weight from hatching until 6 weeks of age for chicks hatched from eggs exposed to different thermal conditioning regimes. Sengor et al 41 exposed eggs to TC at 39 °C for 2 h per day at E14 and E15, while 42 subjected eggs to 39.6 °C or 40.6 °C.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, studies by 41 43 , demonstrated that a decrease in body weight from hatching until 6 weeks of age for chicks hatched from eggs exposed to different thermal conditioning regimes. Sengor et al 41 exposed eggs to TC at 39 °C for 2 h per day at E14 and E15, while 42 subjected eggs to 39.6 °C or 40.6 °C. Similarly, Zaboli et al 43 found that thermal conditioning of Ross 308 eggs at 39.5°C and 65% relative humidity for 12 h per day from E7 to E16 led to a decrease in body weight when contrasted with the control group.…”
Section: Discussionmentioning
confidence: 92%
“…Este tipo de efecto se puede minimizar controlando la ventilación en los galpones y regulando su temperatura interna. Sin embargo, para ello se requieren sofisticados diseños de vivienda, que demandan altas inversiones, haciendo inviable su uso en producciones con bajos recursos económicos (Sengor et al, 2008). Cuando la temperatura ambiental (TA) aumenta; activa la zona de termo neutralidad del ave, induciendo una condición de estrés, con la consecuente generación de: hipertermia aguda, alcalosis respiratoria, desequilibrio electrolítico, reducción del consumo, baja tasa de crecimiento y aumento en la mortalidad (Brossi et al, 2009).…”
Section: Introductionunclassified
“…Estudos mostram que o imprinting das funções corporais estimula a eficiência nas granjas. Alguns autores citam a adaptabilidade ao calor em frangos de corte expostos a alterações na temperatura de incubação , enquanto que outros SENGOR et al, 2008) não encontraram efeito no desempenho zootécnico. Diversos estudos têm relatado as consequências de estresse térmico na produção animal nos últimos anos levando em consideração razões de bem-estar animal e índices econômicos.…”
Section: Introductionunclassified